The Way School Leaders Develop Tourism as a Viable Major in Vocational Education in West Papua - Agtisda Tiofanna Silalahi (MATAI: International Journal of Language Education, 2021)
This project examines the West Papuan community’s assumptions regarding the vocational high school major in Tourism, specifically the high school in Manokwari that was established in 2007. Unfortunately, the expectations of the policy makers in the field of vocational education and tourism are not met by the low number of young people who are interested in the school and finally decide to enroll in the school. The Causal Layered Analysis (CLA) used in this study looks at the issues through each of four layers, namely the Litany, Systemic/Social Causes, Discourse/Worldview, and Myth/Metaphor. The analysis moves from the current scenario through the layers to the construction of a new alternative scenario. It is recognized that the school needs innovation in the paradigm of the relational type of leadership model. The recommendations propose four main areas of cooperation through the Appreciative Inquiry approach: 1) within the school, 2) with the community, 3) with the tourism business sector, and 4) with the local Department of Tourism and the Department of Education. The project fills the gap in the literature, which lacks research on tourism vocational high schools in West Papua.